DIGITAL MINDSET DAN KESEHATAN MENTAL REMAJA DI ERA DIGITALISASI: TINJAUAN PSIKOLOGIS - Rehna Ginting, Lusinta; Buulolo, Delviana; Siregar, Nita Permatasari; Aritonang, Marsela Giovani; Marpaung, Lira Septina (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
The rapid development of digital technology has brought significant changes to the way adolescents think, interact, and shape their identities. This situation requires adolescents to have a healthy digital mindset to be able to use technology adaptively and responsibly. This study aims to analyze the relationship between digital mindset and adolescent mental health in the digital era. The research method used was a descriptive qualitative approach using semi-structured interviews with ten adolescents aged 15–18 who actively use social media. Data were analyzed using thematic techniques to identify patterns of adolescents' experiences and perceptions related to digital media use. The results show that a positive digital mindset—characterized by adaptability, self-awareness, and control over technology use—contributes to better mental health. Conversely, an unhealthy digital mindset is correlated with digital fatigue, anxiety, negative social comparison, and decreased academic productivity. This study emphasizes the importance of digital literacy education, family support, and the role of educators in shaping a healthy digital mindset in adolescents to maintain psychological well-being in the digital era.